PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI USAHA KECIL MENENGAH, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN MAMUJU UTARA - Helmi, Helmi (Katalogis, 2016)
The aim of this study; (1) to determine the influence of achievement needs (need for achievement) on the performance of employees at the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of North Mamuju regency; (2) to determine the effect of power needs (need for power) the performance of employees at the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of North Mamuju regency; (3) to determine the effect relationship needs (need for affiliation) on the performance of employees at the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of North Mamuju regency. This type of research inikuantitatif with explanatory approach. This study population of employees of Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of North Mamuju regency with the number 44 with census sampling techniques so that the entire population sampled. Data collection techniques including observation, questionnaires, and documentation, while the technique of data analysis using multiple linear regression. The results showed; (1) The need for achievement, need for power and relationship needs simultaneously (synchronously) effect on the performance of employees of the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of North Mamuju regency. The major effect of 72.5% and the remaining 27.5 explained by another variable to the level of a very strong relationship between the variables of motivation with employee performance; (2) The need for the achievement of partial (individual) effect on the performance of employees of the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of North Mamuju regency; (3) The need for power partially (individual) effect on the performance of employees of the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry Mamuju Utara; (4) The need for relationships partial (individual) effect on the performance of employees of the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry North Mamuju regency.